ANALISIS KESALAHAN SISWA DALAM PENGGUNAAN SIMPLE PRESENT TENSE DI SMP N 5 MANADO - YANTI, ISABELLA FARADILA; WAROUW, MAYA PINKAN; RATTU, JULTJE A.J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ This research is entitled â€œThe Analysis on Studentsâ€™ Error in Using Simple Present Tense at SMP N 5 Manadoâ€. The objectives of this research are to identify, classify, and analyze descriptively type of errors and the errors frequently made by students in using simple present tense at SMP N 5 Manado. This research is expected to help in developing language learning process and to give information about the errors especially in using simple present tense. In this research, the writer used case study method and the theory from Ellis (2003). She categorizes three types of errors in the language learning namely omission, misinformation, and misordering. There were 61 participants involved from two classes of SMP N 5 Manado in VII 6 and VII 7. The writer used a writing test consists of simple present tense material in order to get the data from the student.The result of this research shows that there are several errors that students made in using simple present tense. There are 151 errors and it was classified into omission, misinformation and misordering. The errors of omission include omission of â€“ s/es in ending verb, omission of to be, omission not in negative sentences, omission of to do in negative and question sentences, omission of question mark on question sentences, and omission of object. The errors of misinformation include misinformation of simple present tense verb, misinformation of subject, misinformation of object, misinformation of to be, and misinformation of to do. The errors of misordering include misordering of to do, misordering of to be and 2 combination of errors. The error that frequently made by students is misinformation which was done for 683 times.Â Â Â Â  Keywords: Error Analysis, Simple Present Tense, Omission